Novel 3D collagen scaffolds fabricated by indirect printing technique for tissue engineering. - Liu, C; Xia, Z; Han, Z; Hulley, P; Triffitt, J; Czernuszka, J (2008)
This article reports the mechanical properties and in vitro evaluation of a collagen scaffold fabricated using an indirect 3D printing technique. Collagen scaffolds, featuring predefined internal channels and capillary networks, were manufactured using phase change printing. It was observed that the collagen scaffolds featured internal channels and a hierarchical structure that varied over length scales of 10-400 microm. In vitro evaluation using hMSCs demonstrated that the resultant collagen based scaffolds have the ability to support hMSC cell attachment and proliferation; cells can migrate and survive deep within the structure of the scaffold. The cell numbers increased 2.4 times over 28 days in culture for the lysine treated scaffolds. The cells were spread along the collagen fibers to form a 3D structure and extracellular matrix was detected on the surface of the scaffolds after 4 weeks in culture. The crosslinking treatment enhanced the biostability and dynamic properties of the collagen scaffolds significantly.